Ethnicity theory and experience - edited by Nathan Glazer (Cambridge Harvard University Press, 1975)
This volume launches a far-reaching exploration into the meaning, manifestations, and significance of ethnicity in modern society and politics. The authors seek neither to celebrate nor to deplore ethnicity, but rather to examine it as a basis of social organization which in modern societies has achieved a significance comparable to that of social class. Ethnicity indicates that minority groups around the world are no longer doing what society for hundreds of years has expected them to do―assimilate, disappear, or endure as exotic, troublesome survivors. Instead, their numbers expanded by immigration, their experiences and struggles mirrored to one another by the international mass media, minorities have become vital, highly conscious forces within almost all contemporary societies.
Includes bibliographies and index.
Keywords: Ethnicity